Situation Report: Hungary, 2 June 1964 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Anti-Chinese Campaign The Position of Non-Party People Freedom of the Press to Criticise Marshal Sallal Leave Hungary Delegation of Romanian Parliament Arrives Diplomatic Relations on Ambassadorial Level also with Japan Party Delegation to Easy Germany